2010
DOI: 10.3382/ps.2010-00769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a premolt calcium and low-energy molt program on laying hen behavior and heterophil-to-lymphocyte ratios

Abstract: The objectives of this study were to compare the behaviors, postures, and heterophil-to-lymphocyte ratios (H:L) of laying hens housed in a cage system when offered a Ca premolt treatment and low-energy molt diets vs. a traditional feed withdrawal (FW) treatment during and after molt. A total of 144 Hy-Line W-36 hens (85 wk of age), housed 3 hens/cage (413 cm(2)/hen), were used. Hens were allotted to treatments according to a randomized complete block design, with the cage location and initial BW as the blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the studies of van Krimpem et al (2007) and Dickey et al (2010), different particle sizes and ingredient levels in layer diets did not influence the expression of feather pecking. However, van Krimpem et al (2007) found that layers fed coarser diets, independently of dietary energy and non-starch polysaccharide levels, remained longer at the feeders and engaged less in feather pecking behavior than those fed finer diets.…”
Section: Aggressive Behaviormentioning
confidence: 81%
“…In the studies of van Krimpem et al (2007) and Dickey et al (2010), different particle sizes and ingredient levels in layer diets did not influence the expression of feather pecking. However, van Krimpem et al (2007) found that layers fed coarser diets, independently of dietary energy and non-starch polysaccharide levels, remained longer at the feeders and engaged less in feather pecking behavior than those fed finer diets.…”
Section: Aggressive Behaviormentioning
confidence: 81%